Hepatoprotective Potential of Caesalpinia crista against Iron-Overload-Induced Liver Toxicity in Mice. (17th July 2012) - Sarkar, Rhitajit; Hazra, Bibhabasu; Mandal, Nripendranath
Abstract : The present study was carried out to evaluate the ameliorating effect of Caesalpinia crista Linn. (CCME) extract on iron-overload-induced liver injury. Iron overload was induced by intraperitoneal administration of iron dextran into mice. CCME attenuated the percentage increase in liver iron and serum ferritin levels when compared to control group. CCME also showed a dose-dependent inhibition of lipid peroxidation, protein oxidation, and liver fibrosis. The serum enzyme markers were found to be less, whereas enhanced levels of liver antioxidant enzymes were detected in CCME-treated group. In presence of CCME, the reductive release of ferritin iron was increased significantly. Furthermore, CCME exhibited DPPH radical scavenging and protection against Fe 2+ -mediated oxidative DNA damage. The current study confirmed the hepatoprotective effect of CCME against the model hepatotoxicant iron overload and the activity is likely related to its potent antioxidant and iron-chelating property.